DERTEMINAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS - Putri Adilla; R. Septian Armel; Wira Ramashar (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This study aims to analyze the effect of tax corruption perception, tax justice, E-Billing implementation, and tax socialization on the compliance of individual taxpayers who engage in freelance work. The research was conducted at KPP Pratama Senapelan Pekanbaru using a quantitative method. Data were collected from 100 respondents using probability sampling and analyzed through multiple linear regression. The findings reveal that only the E-Billing implementation variable significantly affects tax compliance among freelancers. Meanwhile, the variables of tax corruption perception, tax justice, and tax socialization have no significant impact. These results highlight the effectiveness of digital tax services in improving taxpayer compliance, especially for freelance workers who often value convenience and efficiency. Therefore, the tax authority should further strengthen electronic-based systems that are more user-friendly, accessible, and tailored to the diverse needs of taxpayers. In addition, improving the quality and relevance of tax education is essential to support long-term compliance across all taxpayer segments.